2008
DOI: 10.1111/j.1600-0501.2007.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Step‐wise analysis of the dental implant insertion process using the finite element technique

Abstract: Through the combination of both dental and engineering expertise, a simplified and efficient modelling technique is developed. This improves the understanding of the biomechanical reaction that the jawbone exhibits due to the insertion of implant. The current research is a pilot study using the FEM to model and simulate the dental implantation process. The assumptions made in the modelling and simulation process are: (1) the implantation process is simulated as a step-wise process instead of a continuous proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…The present study showed similar results to those of a previous study (4), in which the increase of the insertion torque generates higher compressive stress concentrations to the peri-implant bone tissue. In the present study, for the cancellous bone tissue, the increase of insertion torque (from 30 to 80 Ncm) showed an increase of 1175% for the maximum principal stress and 266% for the maximum principal strain.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present study showed similar results to those of a previous study (4), in which the increase of the insertion torque generates higher compressive stress concentrations to the peri-implant bone tissue. In the present study, for the cancellous bone tissue, the increase of insertion torque (from 30 to 80 Ncm) showed an increase of 1175% for the maximum principal stress and 266% for the maximum principal strain.…”
Section: Discussionsupporting
confidence: 91%
“…These failures may have biological causes, such as periimplantitis and systemic diseases. In addition, biochemical factors can negatively influence implant success; for instance, bone over heating during the surgical procedure, occlusal overload, besides the effects of tensile strength, shear and compressive stresses in the peri-implant bone tissue (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leaders represented the five elements of the system under investigation (fixture and abutment screw connection for the implant; cancellous and cortical bone). Taking into consideration the limitations of the materials, we calculated the percentages of all elements survival (17,(20)(21)(22). It was considered as the yield strength of the titanium alloy grade 4 a value of 550 MPa.…”
Section: Discussionmentioning
confidence: 99%